2021
DOI: 10.1038/s41598-021-02066-9
|View full text |Cite
|
Sign up to set email alerts
|

High-titer rheumatoid factor seropositivity predicts mediastinal lymphadenopathy and mortality in rheumatoid arthritis-related interstitial lung disease

Abstract: Rheumatoid arthritis-related interstitial lung disease (RA-ILD) is a common connective tissue disease-related ILD (CTD-ILD) associated with high morbidity and mortality. Although rheumatoid factor (RF) seropositivity is a risk factor for developing RA-ILD, the relationship between RF seropositivity, mediastinal lymph node (MLN) features, and disease progression is unknown. We aimed to determine if high-titer RF seropositivity predicted MLN features, lung function impairment, and mortality in RA-ILD. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…However, the imperfect predictive ability of these clinical features raises the question of whether additional factors may provide further prognostic information. RF and ACPA presence have previously been associated with increased mortality in RA and RA‐ILD, 27,28 but their prognostic impact in other ILD subtypes is unknown. We found that seropositivity was associated with increased PF‐ILD in IPF and unclassifiable ILD, whereas seropositivity was associated with slower FVC decline in HP.…”
Section: Discussionmentioning
confidence: 99%
“…However, the imperfect predictive ability of these clinical features raises the question of whether additional factors may provide further prognostic information. RF and ACPA presence have previously been associated with increased mortality in RA and RA‐ILD, 27,28 but their prognostic impact in other ILD subtypes is unknown. We found that seropositivity was associated with increased PF‐ILD in IPF and unclassifiable ILD, whereas seropositivity was associated with slower FVC decline in HP.…”
Section: Discussionmentioning
confidence: 99%
“…RF positivity is an established risk factor for ILD development in patients with RA ( 65 67 ). It has been demonstrated that the prevalence and incidence of RA-ILD correlates with serum titers of RF ( 68 ) and high-titer RF is associated with an increased risk of progression and elevated mortality in patients with RA-ILD ( 69 ), along with a more aggressive form of RA with a higher risk of erosions ( 70 ). Moreover, signs of advanced fibrosis at HRCT (including honeycombing) have been associated with RF seropositivity in patients with RA-ILD ( 69 ).…”
Section: Traditional and Novel Biomarkers In Ra-ildmentioning
confidence: 99%
“…Linfonodomegalias axilares e mediastinais podem ocorrer em 20-70% dos pacientes com AR, especialmente naqueles com AR-DPI. (4,28) A fisiopatologia subjacente a essas linfonodomegalias permanece incerta. No entanto, sugere-se que a migração de células imunes da circulação periférica através dos linfonodos mediastinais para os pulmões contribua para a fibrose pulmonar.…”
Section: Linfadenopatiaunclassified
“…Axillary and mediastinal lymph node enlargement may occur in 20-70% of patients with RA, especially in those with RA-ILD. 4 , 28 The biology underpinning this enlargement remains unclear. However, migration of immune cells from the peripheral circulation through mediastinal lymph nodes to the lungs has been suggested to contribute to pulmonary fibrosis.…”
Section: Airway Diseasementioning
confidence: 99%